Associations Between Lipids and Lipid‐Lowering Drug Target Genes and Osteomyelitis: A Mendelian Randomization Analysis - Zhiyi Zhou; Zhehan Yang; Junpan Chen; Minghao Wen; Jiayuan Lei; Wanzhe Liao; Yahan Li; Linghui Liu; Ziyuan Lu (Medicine Advances, 2025)
ABSTRACT Background Lipid metabolism is a key regulator of inflammation in acute and chronic conditions. However, whether dyslipidemia is related to the process of osteomyelitis remains unclear. This study aimed to use a Mendelian randomization (MR) analysis to examine the associations between triglyceride (TG), low‐density lipoprotein cholesterol (LDL‐C), total cholesterol (TC), and osteomyelitis. Additionally, the associations between the genes corresponding to these traits and osteomyelitis were investigated. Methods Genetic variants associated with TG and TC were selected from the Global Lipids Genetics Consortium, while LDL‐C datasets were extracted from the UK Biobank. Specifically, the lipid‐lowering drug target regions were selected as proxies for drug target perturbation. Osteomyelitis was identified according to the FinnGen consortium. We also conducted supplementary analyses using C‐reactive protein genome‐wide association study data to examine the effect of drug targets on this inflammatory marker. Furthermore, we conducted mediation analyses focusing on several risk factors for osteomyelitis. Results No association was found between LDL‐C, TG, or TC concentrations and osteomyelitis. Proprotein convertase subtilisin/kexin type 9 (PCSK9) was significantly associated with a lower risk of osteomyelitis (odds ratio [95% confidence interval] = 0.49 [0.32–0.76], p = 1.60 × 10−3) and a lower concentration of C‐reactive protein (0.94 [0.92–0.97], p = 3.16 × 10−4). We found that waist circumference was an intermediate variable between PCSK9 and osteomyelitis. Conclusions This study does not support a relationship between dyslipidemia and osteomyelitis. PCSK9 is associated with a lower risk of osteomyelitis. Our findings suggest that waist circumference is a potential mediator between osteomyelitis and PCSK9. Additionally, PCSK9 is associated with reduced CRP concentrations.